2018
DOI: 10.1097/j.pain.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the transcriptome of resident spinal microglia after collagen antibody–induced arthritis

Abstract: Supplemental Digital Content is Available in the Text.Glial inhibitors only reverse mechanical hypersensitivity in male mice subjected to arthritis. No obvious arthritis-related transcriptional difference was identified between male and female spinal microglia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 58 publications
2
49
1
1
Order By: Relevance
“…However, BCP has the advantage of also directly attenuating established mechanical allodynia via CB2 receptors, whereas previous preclinical studies show that minocycline cannot attenuate established hyperalgesia and allodynia [78][79][80], which is possibly one of the reasons we postulated [50] for its failure in clinical trials for neuropathic pain [81]. Moreover, BCP alleviates allodynia in both female (current study and in another study [43]) and male mice [42], whereas a recent study showed that minocycline and pentoxifylline could reverse mechanical thresholds in males, but not in female mice [82]. Treatment with drugs that prevent astrocyte and microglia activation has been found to prevent or reduce neuropathic pain in various models [56,[83][84][85].…”
Section: Discussioncontrasting
confidence: 57%
“…However, BCP has the advantage of also directly attenuating established mechanical allodynia via CB2 receptors, whereas previous preclinical studies show that minocycline cannot attenuate established hyperalgesia and allodynia [78][79][80], which is possibly one of the reasons we postulated [50] for its failure in clinical trials for neuropathic pain [81]. Moreover, BCP alleviates allodynia in both female (current study and in another study [43]) and male mice [42], whereas a recent study showed that minocycline and pentoxifylline could reverse mechanical thresholds in males, but not in female mice [82]. Treatment with drugs that prevent astrocyte and microglia activation has been found to prevent or reduce neuropathic pain in various models [56,[83][84][85].…”
Section: Discussioncontrasting
confidence: 57%
“…These authors have also shown that TNF neutralization by intrathecal administration of infliximab, or spinal prevention of microglial activation by minocycline or fluorocitrate injection, ameliorates AIA-induced hypernociception. Similarly, reversion of persistent pain hypersensitivity in a model of collagen antigen-induced arthritis was induced by spinal inhibition of microglia and astrocyte activation after intrathecal minocycline and pentoxifylline administration, respectively (55). In contrast, we did not observe spinal overexpression of TNF, TNFR1, and TNFR2, nor did we observe overexpression of Iba1 + and GFAP + cells, which are glial cell activation markers, during the persistent joint nociception.…”
Section: Discussionmentioning
confidence: 42%
“…The K/BxN model exhibits persistent pain with mechanical hypersensitivity, which does not return to baseline levels during disease progression and outlasts inflammation [155]. Table 2 briefly summarizes the pathology and pain behaviors reported in RA models [134,137,[153][154][155][156][157][158][159][160][161][162][163][164][165][166][167]. CIA, collagen-induced arthritis; CAIA, collagen antibody-induced arthritis; AIA, antigen-induced arthritis; TNF-Tg, tumor necrosis factor transgene; IL-1RA-/-, interleukin-1 receptor antagonist knockout; CII, collagen type II; Ab, antibody; mBSA, methylated bovine serum albumin; GPI, glucose-6-phosphateisomerase; hTNF, human tumor necrosis factor; RA, rheumatoid arthritis; d, day; wk, week(s); Cat S, cathepsin S; FKN, fractalkine; TLR-4, toll-like receptor 4; IL-1RI, interleukin-1 receptor type I; pCREB, phospho-CREB.…”
Section: Behavioral Tests To Assess Pain In Ra Animal Modelsmentioning
confidence: 99%